Reframing the environment domain of the nursing metaparadigm: Exploring space, place, and technology - Epifania Marlene Purisima; Bernardo Oliber Arde Jr; Francis Don Nero; Rozzano C. Locsin; Jed Montayre (Belitung Raya Foundation, 2024)
Metaparadigms differentiate disciplines in terms of how each discipline develops its knowledge and its scholarship. In nursing, four domains comprise the nursing metaparadigm, namely: environment, person, health, and nursing. Of these domains, the environment domain is the least identified. Relating this domain to the broader substantive meaning of geographical-landscape setting of nursing encounters requires further explanation. Through a discursive process the article positions "space and place" referencing the nursing environment. The aim of the article is to clarify and explain the expanding reach of the environment domain, extending its definition while recognizing its range of influence in nursing and healthcare. Distinguishing the nursing environment as a well-established domain of the nursing metaparadigm makes nursing practice more visible, valuable, and relevant. Characterized by its impact on discipline-related knowledge development guiding professional practice, the environment domain assumes an integral "space and place" in human healthcare practice.